Wakefield excitation in plasma-dielectric structures by a sequence relativistic electron bunches - Kiselev, V.A.; Linnik, A.F.; Onishchenko, I.N.; Pristupa, V.I.; Sotnikov, G.V.; Berezina, G.P. (Вопросы атомной науки и техники, 2015)
he results of theoretical and experimental studies of the influence of the plasma in the transit channel of dielectric structure on the efficiency of wakefield excitation by a sequence of relativistic electron bunches are presented. The dielectric structure of circular cross-section with Teflon (ε=2.1; tgδ=2·10⁻⁴) The plasma in the channel dielectric structure is formed by passing bunches of relativistic electrons through the neutral gas as a result of impact ionization and acceleration of plasma electrons in the excited wake wave. It is shown that when the gas pressure in the range 10⁻²…1 Torr, an increase of the amplitude of the excited wakefield due to changes in the topography of the main electromagnetic mode. In the pressure range 0.1…1 Torr observed focusing electron bunches due to the presence of bunches in the decelerating the total longitudinal electromagnetic field and Langmuir wave and at the same time focusing field of the Langmuir wave. Представлены результаты теоретических и экспериментальных исследований влияния плазмы в канале диэлектрической структуры на эффективность возбуждения кильватерных волн последовательностью сгустков релятивистских электронов. В экспериментах использовалась диэлектрическая структура круглого поперечного сечения с диэлектриком из фторопласта (ε = 2,1; tgδ = 2·10⁻⁴). Плазма в канале диэлектрической структуры образуется при прохождении сгустков релятивистских электронов через нейтральный газ в результате ударной ионизации и ускорения электронов плазмы в поле возбуждаемой кильватерной волны. Показано, что при давлении газа в диапазоне 10⁻²…1 Торр наблюдается увеличение амплитуды возбуждаемого кильватерного поля в результате изменения топографии основной электромагнитной моды. В диапазоне давлений 0,1…1 Торр наблюдается фокусировка электронных сгустков, обусловленная нахождением сгустков в тормозящем суммарном продольном поле электромагнитной и ленгмюровской волн и одновременно в фокусирующем поле ленгмюровской волны. Представлені результати теоретичних і експериментальних досліджень впливу плазми в каналі діелектричної структури на ефективність збудження кільватерних хвиль послідовністю згустків релятивістських електронів. В експериментах використовувалася діелектрична структура круглого поперечного перерізу з діелектриком з фторопласту (ε = 2,1; tgδ = 2·10⁻⁴). Плазма в каналі діелектричної структури утворюється при проходженні згустків релятивістських електронів через нейтральний газ у результаті ударної іонізації і прискорення електронів плазми в полі кільватерної хвилі, яка при цьому збуджується. Показано, що при тиску газу в діапазоні 10⁻²…1 Торp спостерігається збільшення амплітуди збуджуваного кільватерного поля в результаті зміни топографії основної електромагнітної моди. У діапазоні тисків 0,1…1 Торp спостерігається фокусування електронних згустків, обумовлене знаходженням згустків у гальмуючому сумарному поздовжньому полі електромагнітної і плазмової хвиль і одночасно в фокусуючому полі плазмової хвилі.